Effects of Internal Fixation for Mid-Shaft Clavicle Fractures on Shoulder Kinematics During Humeral Elevations - Hung, Li-Wei; Lu, Hsuan-Yu; Chang, Chung-Hsun; Chen, Tsan-Yang; Wang, Ting-Ming; Lu, Tung-Wu (Frontiers in Bioengineering and Biotechnology, 2021)
Background: Mid-shaft clavicle fractures account for 35% to 44% of injuries to the shoulder girdle. There is increasing evidence to support surgical repair, but poor functional outcomes have been reported, and associated factors remain unclear. Methods: The 3D poses of the shoulder bones during arm elevations were measured in 15 patients treated for mid-shaft clavicle fractures by open reduction and internal fixation, and in 15 healthy controls. Results & Conclusions: No significant between-side differences were found in the clavicle length after surgery (p>0.05). The patients showed increased scapular protraction at lower elevation angles and reduced scapular retraction at higher elevation angles during frontal-plane elevations, with significantly reduced clavicle retraction (p<0.05), with unaltered scapular rotation and tilt. The ranges of the observed changes were reduced to arm elevations at 60° and 90° in the scapular and sagittal planes. Similar changes were also found on the unaffected side, suggesting bilateral symmetrical compensation. The results suggest that shoulder kinematics in multi-plane arm elevations should be monitored for any signs of compromised bone motions following surgical treatment and that rehabilitative training may be needed on both sides to improve the bilateral movement control of the shoulder complex.